Differentiation value of miR-26b for major depressive disorder, schizophrenia, generalized anxiety disorder - Lingming Kong; Xiaoli Zhu; Liyi Zhang; Shengdong Chen (Indian Journal of Psychiatry)
Introduction: First episode and drug naive schizophrenia (SZ) patients comorbid with major depressive episode and generalized anxiety disorder (GAD) comorbid with major depressive disorder (MDD) are common in clinical practice, overlapping symptomatology during first presentation of MDD, SZ and GAD challenged the diagnostic process. Materials and Methods: This study aimed to investigate the differentiation value of peripheral microRNA-26b expression in 52 patients of MDD, SZ, and GAD, respectively, and 52 controls. Quantitative real-time reverse transcription polymerase chain reaction was used to further verify aberrant miRNAs of previous identified in MDD and investigate expression level of these peripheral miRNAs in SZ and GAD. Results: The expression levels of miR-26b and miR-4743 were significantly upregulated and of miR-4498, miR-4485, and miR-1972 had no significant difference. There were no significant differences of expression levels of miR-26b, miR-4498, miR-4485, and miR-1972 except miR-4743 between SZ patients and control group and of miR-26b, miR-1972, miR-4498, and miR-4485 between GAD group and the controls. The receiver operating characteristic (ROC) curve of miR-26b in MDD patients showed that its sensitivity and specificity for diagnosis were 0.540 and 0.830, respectively, with the area under curve (AUC) being 0.728; the ROC of miR-26b for SZ and MDD differentiation showed that its sensitivity and specificity were 0.580 and 0.710, respectively, with AUC being 0.631; the ROC of miR-26b for GAD and MDD differentiation suggested that sensitivity and specificity were 0.560 and 0.750, respectively, with AUC being 0.637. Conclusion: MiR-26b might have potential value of differentiation biomarker for MDD, SZ, and GAD.